Effect of the pilates method on people with osteoporosis: a systematic review - Rocha, Valéria da Silva; Rocha, Letícia de Barros; Salgado de Oliveira Rocha, Larissa; da Costa Cunha, Katiane; Rocha, Rodrigo Santiago Barbosa; da Silva, Marianne Lucena (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Aging process is a risk factor for the development of several diseases, including osteoporosis. Osteoporosis is a systemic skeletal disorder characterized by an increase in bone fragility that can result in fractures and considerably impact the lives of patients. As a means of preventing the onset of this disease or even reducing the impact of symptoms in cases where already exists, one can choose to practice physical exercises. The Pilates method was developed by Joseph Pilates with the aim of working mind, body awareness, postural control and movements through a single approach. Objectives: The aim of this study was to review in the available literature the effects of the Pilates method on people with osteoporosis. Methods: This is a systematic review of literature carried out through a comprehensive strategy in the databases PubMed, Cochrane, SciELO, Web of Science, Cinahl and Embase in August 2020. Results: Five studies, three clinical trials and 2 studies Observational studies, published between 2012 and 2020, were included in the review. Of a total of 210 participants, all were female and an average age of 61 years. The main factors evaluated in the studies were bone mineral density, pain, functionality and quality of life. Conclusion: The Pilates method was associated with pain relief, improved functionality and quality of life, and obtaining bone mineral density in women with osteoporosis.